The impact of CPF on direct exports - Lee, Karen Ling Ling (2015)
In this report, we will analyze the economic impact of changes in CPF contribution rates on the direct exports of the manufacturing industry. The area which we will focus on is the effects of CPF on direct exports of labour intensive industries and capital-intensive industries. We will determine whether direct exports of labour-intensive industries are affected more than capital-intensive industries by a change in CPF contribution rates. If these industries are more affected, but can substitute capital for labour with relative ease, the impact of the change in CPF rates on their direct exports will be smaller. We will examine this impact of CPF using six pre-selected labour-intensive industries. Our findings showed evidence which is consistent with our objective above.